P443Investigating coronary effluent transfer as a valid model of remote ischaemic conditioning: the role of stromal derived factor one alpha (SDF-1alpha) and nitric oxide. (15th July 2014) - Pickard, J M J; Davidson, SM; Yellon, DM
Abstract: Background: Remote ischaemic conditioning (RIC) is a phenomenon of great potential clinical significance, being a non-invasive method to limit lethal reperfusion injury. Moreover, the identity of the putative cardioprotective factor, released from the remote organ, has been the subject of many recent studies. In this regard, cardioprotection via transfer of coronary effluent is increasingly being used as a model of RIC, as it is well suited to investigating the humoral factor. Whether it is a valid model of RIC, however, is yet to be determined. This study aimed to elucidate this point, using both a protein recently shown to be involved in RIC in vivo 1, SDF-1α, and a molecule shown to be necessary in inducing the protective phenotype, nitric oxide (NO). Methods: Langendorff perfused male Sprague-Dawley rat hearts were randomly assigned to paired donor/recipient protocols. Coronary effluent was collected during stabilisation (Ceff) or during a preconditioning protocol of 3x5min global ischaemia and 5 min reperfusion (IPCeff). Recipient hearts were perfused with effluent for 10 min prior to 35 min left coronary artery occlusion and 60 min reperfusion. The end point for all experiments was measurement of infarct size as a proportion of area at risk (I/AAR%). Involvement of SDF-1α was assessed via inclusion of AMD3100 (5μg/ml), a specific CXCR4 inhibitor, in the effluent. Similarly, involvement of NO was assessed via inclusion of the NOS inhibitor N (G)-nitro-L-arginine methyl ester (L-NAME) (100μM) in the effluent. Results: IPCeff significantly reduced infarct size from 41±5% (Ceff) to 22 ±6%, (N=7, p<0.0001). IPCeff also caused a significant increase in coronary flow rate (28±4%, p<0.0001 vs. Ceff). AMD3100 did not inhibit IPCeff-mediated cardioprotection (25±2%, p>0.05 vs. Ceff), although interestingly it further augmented coronary flow by 54±5% (p<0.01). L-NAME (100μM) inhibited IPCeff-mediated protection (I/AAR=36±5%, p>0.05 vs. Ceff), and abrogated the increase in coronary flow observed with IPCeff. Conclusions: These data raise interesting questions regarding the universality of an organ/tissue's response to an RIC stimulus. Although the end-effector protective signalling pathways seem to be similar, it is possible that each organ or tissue releases a somewhat different profile of proteins. Indeed, our data suggest just that, with SDF-1α seemingly not involved in intercardiac protection. However, the dependence on NOS activity for protection is in line with the current paradigm. Thus, those who use intercardiac protection as a model of RIC must do so with caution.